J. Irwin Miller : The Shaping of an American Town - Kriplen, Nancy (Book collections on Project MUSE., 2019)
J. Irwin Miller: The Shaping of An American Town' tells the life story of this remarkable man who led Cummins Engine Company from its roots as a small, family business to an international Fortune 500 company and transformed Columbus, Indiana, into a gem of midcentury modern architecture. As president and then chairman of Cummins, Miller emphasized a corporation's responsibility to the community in which it was located and its other stakeholders. Miller's commitment to Columbus architecture inspired such legends as I.M. Pei, Eliel and Eero Saarinen, Kevin Roche, and others to contribute their designs to what has become one of the most artistically revolutionary towns in the country. Columbus's unique public art and architecture continue to inspire young architects and attract visitors from around the world.